Anti-tumor activity and related mechanism study of Bacillus Polymyxa transformed Panax ginseng C. A. Mey. (September 2018) - Gao, Yugang; Liu, Jingting; Ji, Qing; Zhao, Yan; Zang, Pu; He, Zhongmei; Zhu, Hongyan; Zhang, Lianxue
Graphical abstract: Highlights: Ginsenosides are transformed by the Bacillus polymyxa. Converted products are used for anti-tumor experiments in vivo for the first time. The conversion products have a better anti-tumor effect than the ginseng group. The conversion products significantly improve the organ index of mice. Abstract: Panax ginseng C. A. Mey has a history of drug use for thousands of years, and ginsenoside is the main active ingredient. Whether the conversion products of ginseng by Bacillus polymyxa can enhance the anti-tumor activity is to be further studied. This paper aims to study the anti-tumor activity of transformed ginsenoside products by Bacillus polymyxa in vivo and vitro, the results were as follows: In vitro, apoptosis mainly occurred in the late stage for breast cancer cells MCF-7, and the conversion products had better anti-tumor effect than ginseng group ( P < 0.05). In vivo, Compared with the model group, the low, medium and high dose group could inhibit the growth of H22 tumor, improve the organ index of mice, promote the H22 tumor apoptosis ( P < 0.05), increase the proliferation activity of lymphocyte cells and CD4 + /CD8 + ratio, improve the contents of IgG, IgM, IgE, TNF-α, IFN-γ, IL-2, IL-6, IL-12, decrease TGF-β that can inhibit IL-2 in serum. The conversion products could enhance cell immunity, organ immunity, humoral immunity and anti-tumor effect. In particular, TNF-α activity was increased while TGF-β was reduced. Positive drug 5-FU had the effects of improving cell and organ immunity, but also had certain side effects.